Pengaruh Program Reality Show Kepolisian terhadap Sikap Penonton di Jakarta - Panji Andika Raspati; Endang Setiowati (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Every television program consumed by the audience will have an impact on the audience, including the formation of audience attitudes about the issues presented by the program. This study aims to determine the audience's attitude about traffic signs, after consuming the Police reality show program entitled